Cross-Linked Chitosan as an Eco-Friendly Binder for High-Performance Wood-Based Fiberboard - Erzhuo Huang; Yanwei Cao; Xinpeng Duan; Yutao Yan; Zhe Wang; Chunde Jin (International Journal of Polymer Science)
High-performance wood-based fiberboards with high strength and dimensional stability were fabricated by hot-pressing method using 2,5-dimethoxy-2,5-dihydrofuran (DHF) cross-linked chitosan (CS) as an eco-friendly binder. The effects of cross-linked chitosan on the mechanical properties and dimensional stability of wood-based fiberboards were investigated. It is evident that cross-linked chitosan addition was effective in improving mechanical properties and dimensional stability of wood-based fiberboards. The prepared wood-based fiberboard bonded by DHF cross-linked CS displayed optimum modulus of rupture (MOR) of 42.1 MPa, modulus of elasticity (MOE) of 3986.0 MPa, internal bonding (IB) strength of 1.4 MPa, and thickness swelling (TS) value of 16.3%. The improvement of physical and mechanical properties of wood-based fiberboards could be attributed to the amide linkages and hydrogen bonds between wood fibers and cross-linked chitosan. The high-performance wood-based fiberboards fabricated in this study may be a promising candidate for eco-friendly wood-based composites.